Northern Ojibwa Land Tenure - Sieciechowicz, Krystyna (Anthropologica, 2022)
Research on mapping in northern Ontario, Canada has revealed two critically different patterns of land use for two adjacent Cree Indian communities with roughly equal populations but dramatically different histories. These two communities do not replicate historical correlates of land use in the manner projected in the land tenure literature for the eastern Subarctic over the past fifty years. It is suggested that factors such as social structure and organization may be more significant in determining land use patterns than those indicated in the literature.